Students’ Social Literacy in their Daily Journal - Az-Zahra, Hafni Resa; Sarkadi, Sarkadi; Bachtiar, Ishak Gary (Universitas Pendidikan Indonesia, 2018)
This study was aimed to determine the students’ social literacy in their daily journals at grade four of Al-Fauzien Islamic Elementary School in Indonesia. The ability of social literacy is the capacity of a person to be able to live and contribute to his or her community, which involved intellectual skills, social skills, cooperative skills, and attitudes and values. The student's daily journal is a collection of student writings whose contents expose students' skills in reflecting experiences, findings, critical thinking, connecting ideas, exploring and expressing their knowledge. The method used in this study is a qualitative method with qualitative content analysis techniques. The data of this study are the sentences taken from students 'daily journals, which were then reduced, coded based on students' social literacy aspects that appeared and analyzed, then triangulated. The results of the study revealed the ability of students’ social literacy as follows: intellectual skills 34.1%, social skills 12.6%, cooperation skills 14.7%, and social attitudes and values 38.5%.